The effect of job aids on knowledge retention among Patent and Proprietary Medicine Vendors trained to administer injectable contraceptives: longitudinal results from implementation science in Nigeria - Sara Chace Dwyer; Aparna Jain; Salisu Mohammed Ishaku; Faizah Tosin Okunade; Chiamaka Uzomba; Adedamola Adebayo; Elizabeth Tobey (BMC, 2019)
Abstract Background To increase access to voluntary family planning (FP) services, Nigerian policymakers are debating how to task share injectable contraceptive services to drug shop owners known as Patent and Proprietary Medicine Vendors (PPMVs). Task sharing FP services to drug shops is a promising practice, but information is needed on how to ensure high quality FP services. This analysis assesses the effects of job aids on PPMVs' knowledge of injectable contraceptives 9 months after receiving a standardized training. Methods One hundred ninety-four PPMVs were trained on FP counseling and administration of injectable contraceptives in Bauchi, Cross River, Ebonyi and Kaduna states. PPMVs were interviewed before, after, and 9 months after the training. Three variables were used to assess injectable contraceptive knowledge: 1) intramuscular depot-medroxyprogesterone acetate (DMPA-IM) knowledge: a combination of three questions related to device type, injection location, and reinjection frequency; 2) subcutaneous DMPA (DMPA-SC) knowledge: a combination of the same three questions but for DMPA-SC; and 3) knowledge of at least 4 of the 7 common injectable side effects. Three separate adjusted logistic regression models were conducted to determine the factors that influence PPMV knowledge of injectable contraceptives 9 months after the training. Results Over half of PPMVs (56%) reported using at least two job aids at 9 months. PPMVs' knowledge of DMPA-IM, DMPA-SC and side effects were low before the training but increased immediately after. Nine months later, knowledge remained higher than pre-test levels but generally reduced compared to posttest levels. PPMVs who reported using at least two FP job aids were 2.6 (95% CI: 1.4-5.1) times more likely to have DMPA-IM knowledge 9 months after the training compared to those who used one or no job aids, while adjusting for PPMV characteristics. Similar results were observed for knowledge of DMPA-SC (AOR: 2.5; 95% CI: 1.2-4.6) and side effects (AOR: 2.5; 95% CI: 1.3-4.8). Conclusion PPMVs who used at least two FP job aids were more likely to correctly answer key injectable contraceptive questions 9 months after training. Incorporating proven job aids into routine trainings is a low-cost strategy that can reinforce knowledge and help PPMVs to retain information.